Euler-Savari Determination of Radii of Curvature of Cycloid Profiles; Russian Engineering Research; Vol. 30, № 10 - Efremenkov (Ephremenkov) E. A. Egor Alekseevich (2010, 2010)
The radius of curvature of a cycloid tooth profile is determined on the basis of the Euler-Savari theorem, without using profile equations. The formulas obtained may be used to determine radii of curvature of other cycloid couplings in which one of the contact profiles is a circle. A sample calculation is presented.